Self-study mobile-assisted language learning and students’ English writing strategies - Nofvia De Vega; Sahril Nur; Ismail Anas; Rahayu (UNIB Press, 2025)
This paper explores the way the demographic factors, usage behaviours, and learning strategies of English writing students affect their proficiency in writing by using Mobile-Assisted Language Learning (MALL) tools. In particular, it poses the following question: How do the demographics, MALL use patterns, and learning strategies of the learners interact to influence their proficiency in writing English? The online questionnaire was used to gather data on 124 university students in Kalimantan. Descriptive analysis showed that 67 per cent of the participants are female, with a majority of them being aged 18 to 20 years. Most of them applied MALL tools to train text types (28 percent), improve the writing style (21 percent), and grammatical accuracy (19 percent). The findings have shown great scores of self-direction (86%), problem-solving orientation (79%), which portrays proactive and reflective learners. All of those strategies were related to enhanced writing abilities at all levels. The conclusion of the paper is that the integration of the MALL tools can enhance self-directed and problem-based learning in writing classes. The results provide a helpful contribution to educators in the creation of adaptive and strategy-based MALL-assisted instruction writing.